Analisis Siswa Autisme di SDN Keroncong MAS Permai - Nurfadhillah, Septy; Adinda, Astri Putri; Shafani, Hesty Tri; Ramadhani, Vira; Utami, Wahyuni Desti; Insani, Intan Khairul; Refando, Ardy; Wijaya, Rizky Rahman (Lembaga Yasin AlSys, 2022)
Children with special needs are children with special characteristics that are different from children in general without always showing mental, emotional or physical disabilities. Included in the ABK include: visually impaired, deaf, mentally retarded, physically disabled, mentally retarded, learning difficulties, behavior disorders, gifted children, children with health problems. Other terms for children with special needs are extraordinary children and disabled children. Autism is defined as a disorder that affects development and is complex in nature regarding the activities of imagination, communication and social interaction. This study aims to analyze Autism students at SDN Keroncong Mas Permai to find out what Autism is, what are the weaknesses and strengths of Autism children, and how to handle it in learning. This research method is observation with a descriptive approach that is explaining the problems in the field. This data collection technique is observation, interview and documentation. The results of this study that there are students with special needs in class IV are students with autism. This can be seen when students interact and communicate. So it can be concluded that there are children with special needs in grade IV at SDN Keroncong Mas Permai with autism.